2023
DOI: 10.1038/s41598-023-34742-3
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of CdS/CeO2 heterojunction nanocomposite with tunable bandgap for the enhanced advanced oxidation process

Abstract: Herein, a binary nanocomposite CdS/CeO2 has been fabricated via a one-pot co-precipitation method for the degradation of Rose Bengal (RB) dye. The structure, surface morphology, composition, and surface area of the prepared composite were characterized by transmission electron microscopy, scanning electron microscopy, X-ray powder diffraction, X-ray photoelectron spectroscopy, Brunaur–Emmett–Teller analysis UV–Vis diffuse reflectance spectroscopy and photoluminescence spectroscopy. The prepared CdS/CeO2(1:1) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…DMF has good solubility for polymers to a certain extent and can diffuse into the interior of epoxy polymers and cause swelling, leading to depolymerization and dissolution of epoxy oligomers. 36,37 The results showed that the CERBs have a good reusability for the removal of CR.…”
Section: Resultsmentioning
confidence: 97%
“…DMF has good solubility for polymers to a certain extent and can diffuse into the interior of epoxy polymers and cause swelling, leading to depolymerization and dissolution of epoxy oligomers. 36,37 The results showed that the CERBs have a good reusability for the removal of CR.…”
Section: Resultsmentioning
confidence: 97%
“…In the present study increased the catalyst dosage from 0.025, 0.05, 0.1, and 0.2 g/20 mL, the degradation percentage of MB dye initially increased which may be attributed to the active ROS sites generation. But in higher dosage of catalyst 0.2 g degradation percentage of MB dye decrease, and it could be due to the decrease in photon penetration on the catalyst surface block in solution which leads to a decrease the formation of ROS 60 .
Figure 10 ( a ) Change in the concentration of MB dye in different catalytic dosage in presence of JC-La 2 CoO 4 .
…”
Section: Resultsmentioning
confidence: 99%
“…The rate of degradation in presence of IPA and AA rate is highest, therefore the ˙OH, and O 2 - species play a key role for the degradation 60 , 64 , 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Metal sulfates, especially those based on cadmium sulfide, are highly appreciated for their suitable energy band alignment and low band gap (∼2.4 eV), which makes them useful for photodegradation reactions. 54 Unfortunately, low solar energy use and the quick recombination of photogenerated electron–hole pairs limit the efficiency of cadmium sulfide. The addition of more metals to create solid solutions is thought to be a workable solution to this problem.…”
Section: Enhancement Of Photocatalytic Efficiencymentioning
confidence: 99%